2016
DOI: 10.1016/j.jphys.2016.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Exercise improves glycaemic control in women diagnosed with gestational diabetes mellitus: a systematic review

Abstract: PROSPERO CRD42015019106. [Harrison AL, Shields N, Taylor NF, Frawley HC (2016) Exercise improves glycaemic control in women diagnosed with gestational diabetes mellitus: a systematic review.Journal of Physiotherapy62: 188-196].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(57 citation statements)
references
References 48 publications
1
52
0
4
Order By: Relevance
“…In addition, for those with GDM, light walking for 25 to 40 minutes, three or four times a week, resulted in a decrease in the need for insulin, and there are suggestions that the best results may be achieved with vigorous intensity exercises . Resistance training for muscular endurance has also been reported to reduce the need for insulin, as well as insulin doses, in women with GDM and in women with GDM who are overweight, including when performed with moderate to vigorous intensity exercise, 20 to 30 min/session, 3 to 4 d/wk . However, our findings indicated that less than half the participants received counseling for physical activity practice before or after the diagnosis of GDM, behavior that could help in the management of GDM.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…In addition, for those with GDM, light walking for 25 to 40 minutes, three or four times a week, resulted in a decrease in the need for insulin, and there are suggestions that the best results may be achieved with vigorous intensity exercises . Resistance training for muscular endurance has also been reported to reduce the need for insulin, as well as insulin doses, in women with GDM and in women with GDM who are overweight, including when performed with moderate to vigorous intensity exercise, 20 to 30 min/session, 3 to 4 d/wk . However, our findings indicated that less than half the participants received counseling for physical activity practice before or after the diagnosis of GDM, behavior that could help in the management of GDM.…”
Section: Discussionmentioning
confidence: 58%
“…11,36 Resistance training for muscular endurance has also been reported to reduce the need for insulin, as well as insulin doses, in women with GDM 37 and in women with GDM who are overweight, 38 including when performed with moderate to vigorous intensity exercise, 20 to 30 min/session, 3 to 4 d/wk. 9 However, our findings indicated that less than half the participants received counseling for physical activity practice before or after the diagnosis of GDM, behavior that could help in the management of GDM. Counseling for GDM women is an important intervention for management of the condition.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In a current interventional study of a Chinese cohort of obese pregnant women it was shown that regular exercise (in this case cycling) was able to reduce the risk of developing gestational diabetes and excessive weight gain during pregnancy without increasing the risk of premature birth [18]. In addition, a systematic review showed that regular exercise can improve postprandial glucose levels in women with known gestational diabetes [19]. A further protective effect attributed to exercise is with regards to the development of preecclampsia: Various studies report an inverse relationship between higher prenatal exercise levels and reduced risk of preecclampsia [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Nonpharmacological measures are critical to the early stages of diabetes mellitus, but people who often ignore the importance of nonpharmacological measures are often ignored, while pharmacological measures are the most frequently used therapies at this stage and the goal would be to have a drug ameliorate or correct both of these abnormalities in the patient with diabetes mellitus. Fortunately, multitudinous research continues to furnish advanced understanding of the pathophysiology and outcomes of this disease, which could help patients to change views and to control diabetes mellitus better with proper diet, applicable exercise, and advisable weight control [31]. All of these are the principles of management of diabetes; management of DN could be fit for the same principles.…”
Section: Prevention and Management Of Dnmentioning
confidence: 99%